2004
DOI: 10.3402/tellusa.v56i3.14413
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of observation impact using the NRL atmospheric variational data assimilation adjoint system

Abstract: An adjoint-based procedure for assessing the impact of observations on the short-range forecast error in numerical weather prediction is described. The method is computationally inexpensive and allows observation impact to be partitioned for any set or subset of observations, by instrument type, observed variable, geographic region, vertical level or other category. The cost function is the difference between measures of 24-h and 30-h global forecast error in the Navy Operational Global Atmospheric Prediction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
167
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(175 citation statements)
references
References 8 publications
4
167
0
Order By: Relevance
“…has been first considered in the work of Langland and Baker (2004) and in recent adjoint-based OBSI studies (Cardinali, 2009;Gelaro and Zhu, 2009). Efficient alternatives to (11), such as a midpoint rule, are discussed by Daescu and Todling (2009).…”
Section: Adjoint-das Observation Impact Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…has been first considered in the work of Langland and Baker (2004) and in recent adjoint-based OBSI studies (Cardinali, 2009;Gelaro and Zhu, 2009). Efficient alternatives to (11), such as a midpoint rule, are discussed by Daescu and Todling (2009).…”
Section: Adjoint-das Observation Impact Estimationmentioning
confidence: 99%
“…Adjoint-DAS estimation of the observation sensitivity was considered in the work of Baker and Daley (2000) and Doerenbecher and Bergot (2001) as a tool to design observation targeting strategies. Subsequently, Langland and Baker (2004) have shown that the combined information derived from the adjoint of the forecast model and the adjoint-DAS may be used to provide a detailed (all-at-once) assessment of the observation impact on reducing the forecast errors in variational data assimilation (VDA). Adjoint-DAS tools have been developed at major NWP centres and are currently used to monitor the impact of data provided by the global observing network in reducing short-range forecasts errors, to provide data quality diagnostics and guidance for optimal satellite channel selection, and to design observation targeting strategies Fourrié et al, 2002;Langland, 2005;Zhu and Gelaro, 2008;Baker and Langland, 2009;Cardinali, 2009;Gelaro and Zhu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Baker and Daley (2000) have shown that an all-at-once evaluation of the forecast sensitivity to observations may be performed by developing the adjoint of the data assimilation system (adjoint-DAS). The analysis of the information content of observations and the observation impact assessment through observation sensitivity and adjoint-DAS techniques are routine activities at NWP centres to monitor the observing system performance on reducing the short-range forecast errors (Langland and Baker, 2004;Trémolet, 2008;Baker and Langland, 2009;Cardinali, 2009;Daescu and Todling, 2009;Gelaro and Zhu, 2009;Gelaro et al, 2010;Cardinali and Prates, 2011;Lupu et al, 2011). The adjoint-DAS applications may be extended to incorporate the sensitivity analysis with respect to error covariance parameters and the estimation of the forecast impact from adjusting the error covariance models.…”
Section: Introductionmentioning
confidence: 99%
“…This is called the targeted observations technique. Different techniques for the placement of obser-vations in the context of numerical weather prediction models are discussed in [9,78,66,49,77,72,7]. Studies performed during field experiments revealed the potential benefits that may be achieved using adaptive observations as well as various practical issues and shortcomings of the current targeting methodologies.…”
Section: Optimal Placement Of Observationsmentioning
confidence: 99%
“…This may be achieved in a posteriori analysis and data assimilation experiments that are used to provide valuable insight on the benefits and shortcomings of various targeted observations strategies. Langland and Baker use forecasts of different lengths that verify at the same time to define J v and to assess the observation impact on the forecast error [66].…”
Section: Optimal Placement Of Observationsmentioning
confidence: 99%